Treatment of an Acute Mycotic Aneurysm of the Common Carotid Artery with a Covered Stent-Graft - Lee, Suk Hoon (Yonsei University College of Medicine, 2012)
We report herein a case successful endovascular treatment with a stent-graft of a rare case of rapidly growing mycotic aneurysm of the left common carotid artery due to acute bacterial endocarditis after eradication of the infection. Infected mycotic aneurysms of the peripheral vasculature have been considered as a contraindication for stent-graft implantation because of the possibility of microorganism spreading to the stent-graft; however, if there is evidence of complete eradication of microorganism and surgery is not an option, stent-graft implantation can be an effective and safe treatment modality for exclusion of the mycotic aneurysm.